Hemocyte response to treatment of susceptible and resistant Asian corn borer (Ostrinia furnacalis) larvae with Cry1F toxin from Bacillus thuringiensis - Prabu, Sivaprasath; Jing, Dapeng; Jurat-Fuentes, Juan Luis; Wang, Zhenying; He, Kanglai (Frontiers in Immunology, 2022)
Midgut receptors have been recognized as the major mechanism of resistance to Cry proteins in lepidopteran larvae, while there is a dearth of data on the role of hemocyte's response to Cry intoxication and resistance development. We aimed at investigating the role of circulating hemocytes in the intoxication of Cry1F toxin in larvae from susceptible (ACB-BtS) and resistant (ACB-FR) strains of the Asian corn borer (ACB), Ostrinia furnacalis. Transcriptome and proteome profiling identified genes and proteins involved in immune-related (tetraspanin and C-type lectins) and detoxification pathways as significantly up-regulated in the hemocytes of Cry1F treated ACB-FR. High-throughput in vitro assays revealed the binding affinity of Cry1F with the tetraspanin and C-type lectin family proteins. We found significant activation of MAPKinase (ERK 1/2, p38α, and JNK 1/2) in the hemocytes of Cry1F treated ACB-FR. In testing plausible crosstalk between a tetraspanin (CD63) and downstream MAPK signaling, we knocked down CD63 expression by RNAi and detected an alteration in JNK 1/2 level but a significant increase in susceptibility of ACB-FR larvae to Cry1F toxin. Information from this study advances a change in knowledge on the cellular immune response to Cry intoxication and its potential role in resistance in a lepidopteran pest.